Generalised method of moments with latent variables - A. Ronald Gallant; Raffaella Giacomini; Giuseppe Ragusa (Centre for Microdata Methods and Practice (cemmap), 2013)
The contribution of generalized method of moments (Hansen and Singleton, 1982) was to allow frequentist inference regarding the parameters of a nonlinear structural model without having to solve the model. Provided there were no latent variables. The contribution of this paper is the same. With latent variables.
Keywords: C32; C36; E27; 330; Generalized Method of Moments; Latent Variables; Structural Models; Particle Filter; Momentenmethode; Multivariate Analyse; Theorie